Główne zadania chrześcijańskiej soteriologii w myśli Anzelma z Canterbury - Kempa, Jacek (Śląskie Studia Historyczno-Teologiczne, 2014)
The soteriology of Anselm of Canterbury had a strong influence on theological reflection in the past. In this article we have considered presumed main reason for this state. This major reason is an attempt to explain the salvific action of Christ in a precise and rational way. This account profoundly integrates the most significant elements of the faith of the Church: the radical and universal need for salvation, the unity of God’s justice and mercy, and the uniqueness of the Mediator of salvation. These elements are still relevant also in the contemporary, pluralistic expression of the faith in redemption, that is why Anselm’s teaching may retain its inspiring abilities.